Hard- and soft-tissue profiles of the midface region in patients with skeletal Class III malocclusion using cone-beam computed tomography multiplanarreconstructed image analysis - Bomi Kim; Hyung-Chul Lee; Seong-Hun Kim; Yongil Kim; Woosung Son; Seong Sik Kim (Korean journal of orthodontics (2012), 2018)
Objective: This study examined cone-beam computed tomography (CBCT)-derived multiplanar-reconstructed (MPR) cross-sections to clarify the salient characteristics of patients with skeletal class III malocclusion with midface deficiency (MD). Methods: The horizontal and sagittal plane intersection po-ints were identified for middle-third facial analysis in 40 patients in the MD or normal (N) groups. MPR images acquired parallel to each horizontal plane were used for length and angular measurements. Results: A comparison of the MD and N groups revealed significant differences in the zygoma prominence among female patients. The convex zygomatic area in the N group was larger than that in the MD group, and the inferior part of the midface in the N group was smaller than that in the MD group for both male and female patients. A significant difference was observed in the concave middle maxillary area among male patients. Conclusions: This study was conducted to demonstrate the difference between MD and normal face through MPR images derived from CBCT. Male patients in the MD group had a more flattened face than did those in the N group. Female patients in the MD group showed a concave-shaped lower section of the zygoma, which tended to have more severe MD. These fin-dings indicate that orthognathic surgery to improve skeletal discrepancy requires different approaches in male and female patients.[Korean J Orthod 2018;48(3):143-152] KCI Citation Count: 5